Environmental Factors for the Advancement of Teachers' Self-Efficacy in Professional Development - Saglam, Mehmet Hilmi; Goktenturk, Talha; Demir, Ibrahim; Yazici, Emre (MDPI, 2023)
There is a shifting paradigm in gifted education from person-based approaches (i.e., identifying giftedness) to process-based approaches (i.e., transacting giftedness). This new framework is centered on enriching educational opportunities that will make the process meaningful (i.e., gifted) to everyone in a setting. However, little is known about how this renewed perspective can be applied in teacher professional development. In line with the socio-ecological models, our study aims to identify the best appropriate model to describe teacher self-efficacy (i.e., the dependent variable in the study) as professional development from an ecological perspective and to propose an ecologically intelligent school (EIS) for the advancement of self-efficacy. Structural equation modeling (SEM) was performed to create a model using TALIS 2018 dataset. Afterward, indices of goodness-of-fit criteria were examined for each model. The results indicate that there is a complex ecological background, in that various factors affect the dependent variable. Model 3 was determined as the most suitable model that can be proposed as an ecologically intelligent school (EIS) for the advancement of self-efficacy. The factors within the three layers of the socio-ecological model-communication with teachers, communication with students, school climate, and feeling valued by the national level-altogether created an appropriate model explaining teacher professional development, regarding self-efficacy.
Keywords: teacher professional development; ecologically intelligent school; self-efficacy; structural equation modeling; IMPLICIT THEORIES; EDUCATION; MODEL; ACHIEVEMENT; RELIABILITY; DIMENSIONS; ATTITUDES; SCHOOLS; SEM; Psychology